EXPLORING THE BENEFITS AND CHALLENGES OF ALTERNATIVE EDUCATION - Kadirova Charos Turabovna (INTERNATIONAL JOURNAL OF SOCIAL SCIENCE & INTERDISCIPLINARY RESEARCH ISSN: 2277-3630 Impact factor: 8.036, 2025)
This paper explores the theoretical foundations, historical evolution, diverse forms, and pedagogical implications of alternative education as a transformative response to conventional schooling systems. It provides an in-depth analysis of various models, including Montessori, Waldorf, unschooling, democratic schools, and online learning platforms, with attention to their philosophical underpinnings, operational challenges, and societal impact. Drawing upon global examples, the study highlights both the benefits—such as personalized learning, life skills development, creative expression, and cultural relevance—and the limitations of alternative schooling environments. Furthermore, it underscores the role of student agency, teacher autonomy, and flexible infrastructure in shaping meaningful educational experiences outside traditional paradigms. The conclusion advocates for broader recognition of alternative education’s contributions to educational theory and practice, emphasizing its potential to influence mainstream reforms through inclusive, student-centered innovation.